Exploring and mitigating failure modes in anodes for Li-ion batteries - Schulze, Maxwell C., author; Prieto, Amy L., author (Colorado State University. Libraries, 2017)
Next generation rechargable batteries for electric vehicle and grid energy storage applications require greater energy densities and long cycle lifetimes than tradition intercalation Li-ion batteries. Replacing graphite with alloy anodes shows promise for increasing the lithium storage capacity of batteries, though the anodes suffer from mechanical instability and limited cycle lifetimes. Building off the promising behavior of Cu2Sb alloy anodes for Li-ion batteries, we show how cycle lifetimes of electrodeposited Cu-Sb thin-films can be further improved by controlling undesirable mechano-chemical interactions at the film-substrate interface.
252 - Max C. Schulze